PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN SOFTWARE GEOGEBRA PADA MATERI BILANGAN BULAT - Nur Laili Ariani (JEDMA Jurnal Edukasi Matematika, 2025)
Currently, the development of science and technology is increasingly advanced and has penetrated into various fields of life, including education. Science and technology is expected to be a solution to various learning problems faced by students and educators. One of the math learning media software that can be used is geogebra. The purpose of this study is to describe the process of developing learning media assisted by geogebra software on integer material and to determine the results of developing learning media assisted by geogebra software on integer material. This research uses a research and development model developed by Lee and Owens (2004), namely ADDIE (Analysis, Design, Development, Implementation, Evaluation). The learning media trial was conducted in class VII-A and VII-B SMP PGRI 16 Sidoarjo on May 30, 2024. The results of the assessment on the learning media validation sheet obtained a total average of 0.91 which indicates a very high category. So it can be concluded that the learning media assisted by geogebra software on integer material is valid. The results of observations of learning implementation obtained a percentage of 85.42% which shows learning media in the Practical category. While the results of the usage response questionnaire show a percentage of 72.25%, this figure means that the students' response is in the Moderate category and shows that the learning media is in the Ineffective category.